Evaluasi Penggunaan Obat pada Lansia dengan Rheumatoid Arthritis di Desa Lameue - Syahbuddin Syahbuddin; Yunita Yusnita; Lisma Luciana; T. Khairul Rozi; Yulidar Yulidar; Analia Husna (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Rational medicine use is particularly important in older adults with rheumatoid arthritis (RA), who may face complex regimens, multimorbidity, and a greater risk of adverse drug events. Objective: To evaluate self-reported medication use and examine its associations with knowledge, adherence, and perceived clinical improvement among older adults with RA in Lameue Village, Pidie Regency. Methods: This cross-sectional correlational study included all 45 eligible older adults with RA in the study population (total sampling). Data were collected using a questionnaire reported as valid and reliable. Categorical variables were summarized as frequencies and percentages, and associations were explored using Pearson's chi-square test at a 5% significance level. Results: Medication-use evaluation was predominantly moderate (62.2%). Knowledge was poor in 40.0% of respondents; adherence was good in 35.6%, moderate in 28.9%, and poor in 35.6%. Perceived clinical improvement was moderate in 53.3%. Knowledge (p=0.002), adherence (p=0.024), and perceived clinical improvement (p<0.001) were associated with medication-use evaluation. Several expected cell counts were below five; therefore, the results should be interpreted as exploratory. Conclusion: Knowledge and adherence were associated with better self-reported medication-use evaluation. Structured education, caregiver involvement, medication review, and follow-up may support safer medicine use, but causal and clinical effectiveness claims require confirmation using validated outcomes and robust analyses.